2021
DOI: 10.1002/vms3.440
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial susceptibility profiles of non‐typhoidal Salmonella isolated from chickens in Rajshahi, Bangladesh

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…In our research, we discovered an overall prevalence of Salmonella 18.96% in poultry processing environmental samples such as CDW, CBS, and KS. Previously, in Bangladesh the prevalence of Salmonella was found to be present 23.33% in poultry slaughter specimens [ 23 ]; 26.6% in chicken cloacal swab, intestinal fluid, egg surface, hand wash, and soil of chicken market samples [ 65 ]; 25.35% in the chicken cloacal swab, eggshells, intestinal contents, liver swabs, broiler meat, and swabs of slaughterhouse [ 66 ]; 35% in broiler farms settings [ 31 ]; 23.53% in poultry samples [ 67 ]; 37.9% in poultry production settings [ 68 ]; 31.25% in broiler farm settings [ 69 ]; 42% in broiler chicken [ 70 ] and 65% in frozen chicken meat [ 71 ]. The prevalence of Salmonella was found to be 8.62% in broiler, 6.89% in sonali and 3.1% in native chicken cecal contents according to Siddiky et al [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our research, we discovered an overall prevalence of Salmonella 18.96% in poultry processing environmental samples such as CDW, CBS, and KS. Previously, in Bangladesh the prevalence of Salmonella was found to be present 23.33% in poultry slaughter specimens [ 23 ]; 26.6% in chicken cloacal swab, intestinal fluid, egg surface, hand wash, and soil of chicken market samples [ 65 ]; 25.35% in the chicken cloacal swab, eggshells, intestinal contents, liver swabs, broiler meat, and swabs of slaughterhouse [ 66 ]; 35% in broiler farms settings [ 31 ]; 23.53% in poultry samples [ 67 ]; 37.9% in poultry production settings [ 68 ]; 31.25% in broiler farm settings [ 69 ]; 42% in broiler chicken [ 70 ] and 65% in frozen chicken meat [ 71 ]. The prevalence of Salmonella was found to be 8.62% in broiler, 6.89% in sonali and 3.1% in native chicken cecal contents according to Siddiky et al [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Akond et al [24] reported 100% penicillin-resistant and 88% ampicillin-resistant Salmonella in hand wash, intestinal fluid, cloacal swab, egg surface and soil samples from a layer farm in Dhaka. Sarker et al [45] reported similar results ten years later, both in broilers and layers in Rajshahi. Ampicillin was the first broad-spectrum antibiotic of the penicillin group.…”
Section: Antimicrobial Resistance Profile Of Salmonella 71 Resistance...mentioning
confidence: 64%
“…In this review, we found that 17.19%, 28.57% and 30% of salmonellae were present in water, transport swab and air samples from poultry farm environments in Bangladesh [25,33,39,41]. This study also observed that average 26.30% of the cloacal swab samples, 42% of the visceral organ samples and 60% of intestinal fluid samples were infected with Salmonella [24,32,38,44,45,48]. Salmonella infection in poultry farm samples has been documented from many regions of the world, with rates of 17%, 35%, 36%, 39% and 53% in the United States, Spain, Korea, Brazil and Vietnam, respectively [71,72].…”
Section: Overall Prevalence Of Salmonellamentioning
confidence: 82%
See 1 more Smart Citation
“…The prevalence of Salmonella enterica in layer chicken was 40%. The isolated strains of Salmonella were found resistant against penicillin (100%) and nalidixic acid (100%), followed by sulfamethoxazole-trimethoprim (55%), ampicillin (40%), and amoxicillin (25%) [ 36 ]. Colistin is considered one of the last-resort reserved antibiotics for humans.…”
Section: Resultsmentioning
confidence: 99%